2007
DOI: 10.3201/eid1307.061313
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Pandemics in Singapore, a Tropical, Globally Connected City

Abstract: Pandemic preparedness plans must include cities that are global trading hubs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 17 publications
(21 reference statements)
1
56
0
Order By: Relevance
“…It is possible that the low and potentially unrecognized effect of this pandemic wave precluded identification of an increase in cause-specific deaths or that, alternatively, this elevation in deaths might be associated with a different pathogen. Herald waves occurring during March–August 1918 and associated with excess deaths concentrated among young adults have been reported for New York City ( 4 ), Mexico ( 6 ), Geneva ( 36 ), Copenhagen ( 26 ), the US military ( 26 ), the United Kingdom ( 14 ), and Singapore ( 11 ); these waves align with the laboratory identification of the pandemic influenza A(H1N1) virus from US soldiers in May 1918 ( 37 ). It is possible that other areas of Chile experienced mild pandemic waves during mid-1918 but that such waves could not be detected by using all-age, all-cause death data.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is possible that the low and potentially unrecognized effect of this pandemic wave precluded identification of an increase in cause-specific deaths or that, alternatively, this elevation in deaths might be associated with a different pathogen. Herald waves occurring during March–August 1918 and associated with excess deaths concentrated among young adults have been reported for New York City ( 4 ), Mexico ( 6 ), Geneva ( 36 ), Copenhagen ( 26 ), the US military ( 26 ), the United Kingdom ( 14 ), and Singapore ( 11 ); these waves align with the laboratory identification of the pandemic influenza A(H1N1) virus from US soldiers in May 1918 ( 37 ). It is possible that other areas of Chile experienced mild pandemic waves during mid-1918 but that such waves could not be detected by using all-age, all-cause death data.…”
Section: Discussionmentioning
confidence: 81%
“…Although peak pandemic-related deaths occurred during October–November 1918 in temperate regions of the Northern Hemisphere (autumn) ( 4 6 , 10 11 ), the most lethal pandemic wave in Chile peaked in midwinter (August 1919). This pattern of delayed pandemic deaths in Chile echoes patterns reported from Argentina and Uruguay ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients were followed up for 6 months to observe the development of graft rejection. As a tropical country, Singapore does not have a well-defined influenza season unlike temperate regions (34). An 8-week recruitment period was chosen, because we wanted a 6-month follow-up.…”
Section: Patientsmentioning
confidence: 99%
“…We have shown that the health system resources available to Thailand are likely to be suffi cient to respond to emergent pandemic infl uenza if the pandemic is modest and occurs in a manner similar to the assumptions informing Thailand's simulation exercises. Other countries in the region, which is acknowledged to be at high risk for being at the epicenter of the next global pandemic of infl uenza (25), are likely to have fewer resources than Thailand (3). We are currently investigating the capacity of Thailand and neighboring countries to respond to more profound pandemic infl uenza scenarios.…”
Section: Discussionmentioning
confidence: 99%